2016
DOI: 10.1001/jama.2016.2181
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Early Life and Development of Type 1 Diabetes

Abstract: Viral infections, particularly enteroviruses, 1 have been hypothesized to cause type 1 diabetes (T1D). 2 Recent studies suggest that respiratory tract infections are associated with increased T1D risk if they are encountered within the first 6 months. 3 We explored associations between infection types during the first 2 years and between respiratory tract infections in the first 6 months and T1D in a population-based cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 6 publications
2
54
2
Order By: Relevance
“…Parent-reported early childhood respiratory infections showed no association with islet autoimmunity in a prospective study in the USA [3], whereas respiratory infections were associated with islet autoimmunity in two small European prospective studies; the environmental triggers for type 1 diabetes study (MIDIA) and a primary dietary intervention study to reduce the risk of islet autoimmunity in children at increased risk for type 1 diabetes (BABYDIET) [4, 5]. An analysis of statutory health insurance claims data of individuals from Bavaria, Germany, suggested an association between early life respiratory infections and later clinical type 1 diabetes [6]. Common microbes that cause respiratory tract infections include enteroviruses, which have been reported to show an association with an increased risk of type 1 diabetes [79] and are often found in the pancreatic islets of individuals with type 1 diabetes [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Parent-reported early childhood respiratory infections showed no association with islet autoimmunity in a prospective study in the USA [3], whereas respiratory infections were associated with islet autoimmunity in two small European prospective studies; the environmental triggers for type 1 diabetes study (MIDIA) and a primary dietary intervention study to reduce the risk of islet autoimmunity in children at increased risk for type 1 diabetes (BABYDIET) [4, 5]. An analysis of statutory health insurance claims data of individuals from Bavaria, Germany, suggested an association between early life respiratory infections and later clinical type 1 diabetes [6]. Common microbes that cause respiratory tract infections include enteroviruses, which have been reported to show an association with an increased risk of type 1 diabetes [79] and are often found in the pancreatic islets of individuals with type 1 diabetes [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This review summarize the role of some viruses in the development of type 1 diabetes. Copyright: ©2017 Shaheen between respiratory infections during the early life (first year) of children and islet autoimmunity [27,28]. In Swedish study, the developing islet autoantibodies can be increased in the pregnant woman who infected with enterovirus in early pregnancy [29].…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, fewer infections showed increase in the development of autoimmune disease, while more infections at an early age protected the mice against diabetes (interestingly, infections in some animal models are not necessarily in protection against autoimmune disease) [33]. However, Beyerlein et al [27] reported that the recurrent infection with respiratory virus in the first yrar of life were associated with an increased risk of T1D by age 8.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations